Penatalaksanaan Pemeriksaan Coronary Angiongraphy Pada Kasus Congestive Heart Failure - Muh. Aldi Syaf Badalu; Kusman Kusman (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Management Of Coronary Angiongraphy Examination In Congestive Heart Failure Cases Background : Fail heart congestive heart disease (CHF) is condition inability heart in pump blood consequence disease arteries coroner , who can cause narrowing or blockage arteries heart . Evaluation on CHF patients are very crucial Because can trigger condition fail heart . Coronary angiography, a procedure diagnostic use X- rays and substances contrast , role in identify blockage arteries the coroner who became CHF trigger .Research methods This is literature review, where Exploration literature done in various databases with keywords _ such as Coronary Angiograhy ”, Cases of Congestive Heart Failure, etc. Source reference used _ in preparation This article This includes Google Schollar , as well article in journal scientific Language English nor speak Indonesian. Results: Coronary Angiography (CAG) examination in CHF patients was involved preparation patient , tool , team medical , procedures inspection , maintenance post-action , and results inspection . Preparation patient covers education , fasting , evaluation function kidney , adjustment medicine , preparation access vascular , and discussion about substance contrast . Preparation tool involve table catheterization , fluoroscopy , catheter , substance contrast , equipment resuscitation , medicine pre-procedure , and hemostasis equipment . The medical team involves an interventional cardiologist, radiological technologist, catheterization nurse, catheterization technician, and anesthesia and resuscitation team. The CAG procedure involves patient preparation, vascular access, catheter insertion, coronary artery evaluation, and completion of the procedure. Conclusion : Congestive heart failure (CHF) is caused by the heart's inability to pump blood, especially coronary artery disease. Coronary angiography uses X-rays and a contrast agent to visualize the coronary arteries. Although symptoms of CHF include shortness of breath and swelling, mortality rates remain high, especially over 40 years of age. The role of Coronary angiography in assessment and therapy planning involves medical specialists. The results support effective treatment planning to improve patient prognosis by addressing the causes of CHF.